PREFERENSI MASYARAKAT TERHADADAP BANK SYARIAH DI KOTA MALANG - Hasan, Irmayanti (IQTISHODUNA, 2009)
The result of research indicate that 1) Most society accept attendance of Moslem law bank in its environment is caused by influence mount confidence that Moslem law bank have prospect in the future 2) Preferensi to become client in this time its it[him] still lower because influence of confidence which still lower and religion factor in the reality do not too is having an effect on, beside experience factor less supporting and also not yet been felt by the existence of an requirement 3) At a period to jang will come society potency to become high Moslem law bank client enough, caused by influence of confidence is which are positive supported by religion factor realized that by Moslem law system fitt in with embraced aqidah it and also positive experience factor support. Influence of factor which is signifikan at third the condition especially because of factor confidence of reponden able to have an effect on positive also negativity.